Pengembangan Projectile Launcher Sebagai Alat Praktikum Sederhana Fisika pada Materi Gerak Parabola - Salam, Badru; Latifah, Sri (Universitas Islam Negeri Raden Intan Lampung, 2019)
Abstract:This research is a development research that aims to produce media product projectile launcher as a simple practical tool of physics on parabolic motion material and to know the feasibility of media projectile launcher as a simple practical tool of physics on parabolic motion material. Problems in this research, among others, is how to develop projectile launcher as a simple practical tool of physics on parabolic motion material and how is the response of learners to media projectile launcher as a simple physics practicum tool on parabolic motion material. . Subjects in this study are class IX SMA N 1 Way Tenong and SMA N 2 Way Tenong. This research is a development research using Research and Development (R and D) research method that adopt the development of Borg and Gall that has been modified by sugionoProducts are categorized very feasible based on the validation of material experts with 100% percentage and based on the validation of media experts with a percentage of 100% , as well as Projectile Launcher media are very interesting to be used as teaching materials based on teacher's assessment to get 100% score percentage and student's response in limited group trial to get 95% percentage score for SMA N 1 Way Tenong and 92% for SMA N 2 Way Tenong.Abstrak:Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk menghasilkan produk media projectile launcher sebagai alat praktikum sederhana fisika pada materi gerak parabola dan untuk mengetahui kelayakan dari media projectile launcher sebagai alat praktikum sederhana fisika pada materi gerak parabola. Masalah dalam penelitian ini antara lain bagaimanakah mengembangkan projectile launcher sebagai alat praktikum sederhana fisika pada materi gerak parabola dan bagaimanakah respon peserta didik terhadap media projectile launcher sebagai alat praktikum sederhana fisika pada materi gerak parabola. . Subjek dalam penelitian ini adalah kelas IX SMA N 1 Way Tenong dan SMA N 2 Way Tenong. Penelitian ini merupakan penelitian pengembangan menggunakan metode penelitian Research and Development (R and D) yang mengadopsi pengembangan dari Borg and Gall yang telah dimodifikasi oleh sugionoProduk yang dihasilkan berkategori sangat layak berdasarkan validasi dari ahli materi dengan presentase 100% dan berdasarkan validasi dari ahli media dengan presentase 100%, serta mediaProjectile Launchersangatmenarikuntukdijadikanbahanajarberdasarkanpenilaiangurumemperolehpresentaseskor100% dan respon peserta didik pada uji coba kelompok terbatas memperoleh skor presentase 95% untuk SMA N 1 Way Tenong dan 92% untuk SMA N 2 Way Tenong